1996
DOI: 10.1080/09595239600185611
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the preventive paradox for acute alcohol problems

Abstract: Kreitman's discussion of the preventive paradox in relation to the prevention of alcohol problems has had profound implications for alcohol policy and has generated considerable controversy [1]. It is argued here that although Kreitman should be credited with the important observation that alcohol-related harm is not confined to a few dependent drinkers, none the less an apparent paradox is not an ideal platform from which to recommend policy. Furthermore, Kreitman's own data and data from an Australian survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 12 publications
(18 reference statements)
9
73
0
Order By: Relevance
“…In an Australian population-based survey, Stockwell and colleagues 6 also found support for the prevention paradox, with only 25% of the 67 individuals who reported intoxicationrelated harm exceeding the threshold for hazardous drinking on average. But the phrase "on average" here is key.…”
Section: Introductionmentioning
confidence: 99%
“…In an Australian population-based survey, Stockwell and colleagues 6 also found support for the prevention paradox, with only 25% of the 67 individuals who reported intoxicationrelated harm exceeding the threshold for hazardous drinking on average. But the phrase "on average" here is key.…”
Section: Introductionmentioning
confidence: 99%
“…It is showed, too, that the probabilities of being a victim of predatory crime for females who are weekly or more frequent drinkers are higher than those for males, which could reflect the fact that females, especially those who drink frequently, are more likely to be victims of various crimes [22]. Analyses have shown that the majority of problems may occur in relation to heavy drinking occasions, and that the number of people with heavy drinking occasions is larger among low-moderate consumers than among heavy consumers [28,29,30,144].…”
Section: Discussionmentioning
confidence: 99%
“…This redefinition also shifts the focus of control from individual deviants towards a deviant generation of young bingers. It offers an easy explanation of numerous problems emerging among youngsters: growing discontent, violence, including among young women, football hooliganism and so on [3]. It satisfies cultural demand to explain the alienation of a substantial segment of the young generation in contemporary societies, in particular in individualized societies in the United Kingdom or the United States.…”
Section: Between Symbols and Technicalities -A Concept Of Binge Drinkingmentioning
confidence: 98%
“…Typically, the focus is on distinguishing low-volume (or moderate-volume) drinkers who do and do not engage in RSOD. This distinction was critical for analyses that probed the preventive paradox with respect to alcohol-related problems [2][3][4][5], demonstrating that most problems associated with low and moderate volumes of consumption occurred among drinkers with occasional episodes of RSOD. Less often compared are relatively high-volume drinkers who do and do not engage in RSOD, in part because there are few highvolume drinkers with no RSOD.…”
mentioning
confidence: 99%